Analisis Pengaturan Ketenagakerjaan Pasca Pengesahan Undang-Undang Cipta Kerja dalam Pemutusan Hubungan Kerja (PHK) Sepihak oleh Perusahaan (Studi Kasus Putusan Nomor 229K/Pdt.Sus-Phi/2022) - Ahmad Halim Lubis (CV Rewang Rencang, 2025)
Before the enactment of Law No. 11 of 2020 on Job Creation (Job Creation Law), provisions concerning termination of employment (PHK) were regulated under Law No. 13 of 2003 on Manpower (Manpower Law). The Manpower Law was known for its relatively strict PHK procedures and high severance pay calculations. While these regulations aimed to provide maximum protection for workers, they often faced criticism for potentially hindering investment due to a lack of flexibility in implementation. On the other hand, labor unions and activists consistently emphasized the importance of strong protection to prevent exploitation and ensure worker welfare. This delicate balance between the need for economic growth and the protection of workers' rights formed the primary background for the Job Creation Law's formation. With the enactment of Law No. 6 of 2023, which established Government Regulation in Lieu of Law No. 2 of 2022 on Job Creation as a permanent law, significant changes have occurred in PHK regulations, particularly concerning the mechanism for unilateral terminations by companies. This research employs a normative-empirical (socio-legal) method, utilizing an analytical approach to labor laws and regulations, implementing regulations, labor law doctrines and theories, and case studies based on Supreme Court Decision No. 229K/Pdt.Sus-PHI/2022. The research findings indicate that the Job Creation Law introduces substantive changes in unilateral PHK procedures, characterized by a simplification of the process and a shift in orientation from strict worker protection towards increased corporate flexibility. The new provisions in the Job Creation Law regarding reasons for PHK and compensation significantly reduce the administrative burden on companies and expand employers' authority in making PHK decisions, thereby diminishing workers' bargaining power when facing unilateral terminations